Helophyte impacts on the response of hyporheic invertebrate communities to inundation events in intermittent streams. Issue 6 (6th April 2017) - Baranov, Viktor; Milošević, Djuradj; Kurz, Marie J.; Zarnetske, Jay P.; Sabater, Francesc; Marti, Eugenia; Robertson, Anne; Brandt, Tanja; Sorolla, Albert; Lewandowski, Jörg; Krause, Stefan
Abstract: The effects of experimental inundation on invertebrate communities in artificial flumes fed with treated wastewater were investigated. Flumes, designed to simulate intermittent river conditions, were planted with 3 species of helophytes widely used in river restoration around the water‐stressed regions of Europe. Different species of vegetation had different capabilities to reduce the invertebrate's negative reaction to inundation, related mostly to rhizosphere density. Of the 3 helophyte species tested, only 1, Lysimachia vulgaris, showed significant capabilities to reduce invertebrate negative reaction on inundation. Species richness of invertebrates before and after the inundation did not change in any of the flumes, whereas species density significantly declined in all flumes except one planted with L. vulgaris . This helophyte species was associated with high densities of the Culicidae larvae (common mosquitos), which has severe implications for river restoration and vector management in the region. This study indicates that the selection and establishment of different helophyte species will impact invertebrate communities in restored streams, especially streams experiencing variable inundation conditions.